Experimental investigation of stiffness characteristics of Tee joints of Aluminum Honeycomb core sandwich panels with different edging configurations - Rajkumar, S.; Ravindran, D.; Arul Raj, K.; Pramod Shetty, K. (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Applications and Design in Mechanical Engineering 2012 (ICADME 2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th Februari 2012 at Bayview Beach Resort, Penang, Malaysia